Polyhedrons at the nuclear structure - Aminov, Yu.A. (Вопросы атомной науки и техники, 2017)
The space disposition of nucleons at the light nuclei is given with the help of polyhedrons. At many cases it is the collection of embedded each other regular polyhedrons with nucleons at vertexes. But at the construction one meets other polyhedrons also. We give veri cation of construction by extremal properties of regular polyhedrons.